The evolving social media strategies of politicians in Malaysia: a critical review - Siti Hara Rashid; Fernandez, Kevin (Penerbit Universiti Kebangsaan Malaysia, 2024)
Scholars were optimistic about social media as a tool to reintroduce deliberative democracy. One of the features allows users to express their thoughts and participate in political discussions without being monitored or restricted by the government. It is crucial that politicians also change their communication strategies, including adaptation of social media platforms, to effectively communicate their ideas to their constituents. This study has three objectives. First, it aims to examine the evolution of political strategies used by politicians from conventional media to social media. Second, this study examines the soundbytes that are most popular in the Malaysian context. Third, we seek to understand the perception of ‘media freedom’ amongst politicians and members of the media. Using in-depth interviews with politicians from both sides – the current government and the opposition – this study concludes that Malaysian politicians use social media primarily to portray themselves as people who are loyal to their partners and family, and very religious. Less emphasis is paid on major macro and micro policy debates over social media.